Identifikasi Fitoplankton di Perairan yang Tercemar Lumpur Lapindo, Porong Sidoarjo - NOFADILA Q. A’AYUN; TERRY A. P. PERDANA; PUTRO AJI PRAMONO; AINUN NIKMATI LAILY (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
Some waters are experiencing errors processing till that waters to be waste disposal which resulted in the loss of existing potential, affect water quality and further on the presence of organisms present in the water, especially plankton (phytoplankton) which is the first organisms respond to changes in water quality. One of the pollutants in the water is mud Lapo in Porong, Sidoarjo. This research aims to identify phytoplankton in polluted waters, lapindo mud Porong, Sidoarjo. The method used is the method description. The analysis of samples carried out in the laboratory of Ecology Department of Biology, Faculty of Science and Technology, Maulana Malik Ibrahim State Islamic University Malang . The results of this research was the discovery of 18 species of phytoplankton of the class Chlorophyceae, Trebouxiophyceae, Euglenophyceae, Bacillariophyceae, and from the Division Cyanophyta genus Oscillatoria and Chrococcus.